Academic Integrity: Effects of Demographic Variables on Students’ Conduct - Soroya, Dr Muhammad Shahid; Hashmi, Dr Muhammad Amir; Soroya, Saira Hanif (South Asian Studies, 2020)
This study aimed to find out the effects of demographic variable i.e. gender, age, group of studies, GPA etc. on level of academic integrity among Pakistani students. The design of the study is quantitative in nature, in which the survey research method was employed to gather data from the respondents. A self-reported questionnaire was adapted on the basis of previously developed and validated questionnaire, with the consent of the authors. The developed scale was validated with the help of experts and pilot tested. Multilevel stratified convenience sampling technique was used to collect data from 4 provinces and federal area of Pakistan. The collected data was analyzed by using SPSS 16.0 version
Number: 2
Keywords: dept.ils

Behind the transmitter: differences in archival practices between nonprofit and commercial radio stations - Falcone, Michael; Real, B.; Liu, Y. Q. (Journal of Archival Organization, 2020)
Many radio collections within the United States are maintained in more informal program libraries and archives in hundreds of geographically dispersed broadcasting stations throughout the country. To assess the full extent of this problem and real risk posed to station-owned radio collections, this article assesses the results of a survey administered across twenty-seven nonprofit and commercial stations or corporate parent companies. Nonprofit stations, its findings suggest, are more likely to actively maintain their archives and do so in a manner that shows awareness of current archival standards, whereas commercial stations are less likely to exert active stewardship over their collections. © 2020 The Author(s). Published with license by Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] tex.ids: falconeTransmitterDifferencesArchival2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086264842 type: Article
Keywords: Radio; audio preservation; college radio; dept.ils; peer-reviewed; radio archives; radio preservation

The provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic - Guo, Yajun; Yang, Zinan; Yang, Zhishun; Liu, Yan Quan; Bielefield, Arlene; Tharp, Gregory (Library Hi Tech, 2020)
Purpose: The purpose of this paper is to identify the measures employed in the provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic, noting the challenges and issues inherent in providing substantial services while undergoing a public health emergency. Design/methodology/approach: This paper uses an analytical survey study of 137 Chinese academic libraries using data collected through a combination of website investigation, social media access and direct correspondences. Findings: Over 94% of Chinese academic libraries released COVID-19-related information through their websites; the majority switched their service focus to partly or solely remotely online, including remote access, free electronic resources, virtual references reachable 24/7 and research support services deliverable online; services of print materials were altered to e-books for conveniences. Research limitations/implications: It should be noted that the survey was conducted from February 12 to April 5, 2020; because of the rapid updates to the library's website and social media channels, the status of their patron services are in the process of dynamic changes and that there should be many libraries that have adopted some patron service methods, but this study is difficult to cover comprehensively. In addition, patron services carried out offline by the surveyed libraries but not disclosed on the online platform could not be analyzed in a way that would be consistent with the data provided by the survey. Originality/value: By providing evidence of the current status of patron services in Chinese academic libraries during the COVID-19 pandemic, this study helps fulfill the scant empirical attention given to the impact of nationwide public health crises on academic libraries and offers new data of the best practices that help library administrators enhance the impact, efficiency and value of library services to their target community users. © 2020, Emerald Publishing Limited.
32 citations (Crossref) [2023-10-31] tex.ids: guoProvisionPatronServices2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088570958 type: Article
Keywords: Academic libraries; COVID-19; China; Patron services; Survey; Virtual services; dept.ils; peer-reviewed

Private life, public diplomacy: Tibor Hirsch and documentary filmmaking for the cold war USIA - Real, Brian (Historical Journal of Film, Radio and Television, 2020)
The United States Information Agency acted as a significant patron of American independent and nontheatrical filmmakers during the 1960s, commissioning short documentaries to carry positive messages about America to foreign audiences. While much of the existing scholarship on the USIA’s motion picture output focuses on works that address major policy issues such as the civil rights movement or that were made by directors who went on to have well-known careers, many of its films and directors have been forgotten. One such filmmaker is Tibor Hirsch, whose past as a refugee from the 1956 Hungarian Revolution influenced his films Transportation USA (1966) and Six Who Fled (1972). Hirsch’s earlier career as a photojournalist informed his work for the USIA, while the style he developed through making government films led directly into his later career as a highly successful television commercial director.
0 citations (Crossref) [2023-10-31] tex.ids: realPrivateLifePublic2019, realPrivateLifePublic2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85073924504 type: Article
Keywords: dept.ils; peer-reviewed